2018
DOI: 10.1590/2317-4889201820170095
|View full text |Cite
|
Sign up to set email alerts
|

Melanite-bearing nepheline syenite fragments and 40Ar/39Ar age of phlogopite megacrysts in conduit breccia from the Poços de Caldas Alkaline Massif (MG/SP), and implications

Abstract: The Poços de Caldas Alkaline Massif, located in southeast Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The syenites (nepheline-and alkali-feldspar) would represent the older pulse, and the trachytes and phonolites would represent the more recent pulse. The same pattern (plutonic rocks + volcanic rocks) is also observed in other alkaline bodies of the PCCFA, such as Poços de Caldas, Passa Quatro, Itatiaia, Tinguá, Mendanha, Tanguá, Rio Bonito, and Ilha de Cabo Frio (Amaral et al 1967;Araujo 1995;Brotzu et al 1992;Brotzu et al 1997;Brotzu et al 2007;Chiessi 2004;Enrich et al 2005;Geraldes et al 2013;Guarino et al 2019;Montes-Lauar 1988;Mota et al 2012;Motoki et al 2012;Motoki et al 2013;Sichel et al 2008;Sígolo et al 1992;Silva 2019;Silva et al 2020;Vlach et al 2018).…”
Section: Discussionsupporting
confidence: 60%
“…The syenites (nepheline-and alkali-feldspar) would represent the older pulse, and the trachytes and phonolites would represent the more recent pulse. The same pattern (plutonic rocks + volcanic rocks) is also observed in other alkaline bodies of the PCCFA, such as Poços de Caldas, Passa Quatro, Itatiaia, Tinguá, Mendanha, Tanguá, Rio Bonito, and Ilha de Cabo Frio (Amaral et al 1967;Araujo 1995;Brotzu et al 1992;Brotzu et al 1997;Brotzu et al 2007;Chiessi 2004;Enrich et al 2005;Geraldes et al 2013;Guarino et al 2019;Montes-Lauar 1988;Mota et al 2012;Motoki et al 2012;Motoki et al 2013;Sichel et al 2008;Sígolo et al 1992;Silva 2019;Silva et al 2020;Vlach et al 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Abundant geochronological data obtained by different methods are available for the massif and apparently confirm their long magmatic history (K/Ar age between 64 and 83 Ma, with a median value of 77 Ma, Ulbrich et al 2005). These authors also reported Rb/Sr measurements giving an isochron age of 78.6 ± 6.6 Ma, and more recent work by Vlach et al (2018) yielded an Ar/Ar plateau age of 87 (ca.) Ma for phlogopite crystallization in conduit breccia.…”
Section: Introductionmentioning
confidence: 78%
“…At about 510°C, fine magnetite grains have a relaxation time of about 10 3 Myr (Butler 1992), ensuring that the Cretaceous rocks can preserve the trustworthiness of the acquired magnetization. Therefore, the 89-76 Myr age interval (Vlach et al 2018) based on various methods must be restricted to an 83-76 Myr interval to represent the magnetization polarity better. Ulbrich et al (2002) argued that the best estimation for this massif is about 79 Myr.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, the Poços de Caldas paleomagnetic pole is the more reliable, based on extensive sampling. All studied sites are of reverse magnetization, placing the magmatism outside the CNS, although ages obtained by various methods are in the range of 89-76 Myr (Vlach et al 2018).…”
Section: Introductionmentioning
confidence: 99%